Who You Gonna Call? Gender Inequality in External Demands for Parental Involvement - Kristy Buzard; Laura K Gee; Olga Stoddard (The Quarterly Journal of Economics, 2025)
ABSTRACT Gender imbalance in time spent on child-rearing causes gender inequalities in labor market outcomes, human capital accumulation, and economic mobility. We conduct a large-scale field experiment with a near universe of U.S. schools to investigate a potential source of inequality: external demands for parental involvement. Schools receive an email from a fictitious two-parent household and are asked to call one of the parents back. Mothers are 1.4 times more likely than fathers to be contacted. We decompose this inequality and demonstrate that the gender gap in external demands is associated with various measures of gender norms. We also show that signaling a father’s availability substantially changes the gender pattern of callbacks. Our findings underscore a process through which agents outside the household contribute to within-household gender inequalities.